Detection of Chromosomal Translocation in Hematologic Malignancies by a Novel DNA-Based Looped Ligation Assay (LOLA). (6th January 2020) - Harada, Shuko; Sizzle, Emily; Lin, Ming-Tseh; Gocke, Christopher D
Abstract: BACKGROUND: Disease-defining chromosomal translocations are seen in various neoplasms, especially in lymphomas and leukemias. Translocation detection at the DNA level is often complicated by chromosomal breakpoints that are distributed over very large regions. We have developed a ligation-based assay [the looped ligation assay (LOLA)] to detect translocations from diseases with multiple widely spaced breakpoint hot spots. METHODS: Oligonucleotide sets that probe breakpoints of IGH-BCL2 (immunoglobulin heavy–apoptosis regulator) in follicular lymphoma (FL), MYC-IGH (MYC proto-oncogene, bHLH transcription factor–immunoglobulin heavy) in Burkitt lymphoma (BL) and BCR-ABL1 (RhoGEF and GTPase activating protein–ABL proto-oncogene 1, non-receptor tyrosine kinase) in chronic myelogenous leukemia (CML) were designed. DNA from cell lines with these translocations was mixed with oligonucleotides in a single-step ligation reaction followed by PCR amplification. Detection was by capillary electrophoresis. We also tested peripheral blood from 16 CML patients and frozen tissue from 17 FL cases, and the results were compared to reverse transcription (RT)-PCR (CML) or fluorescent in situ hybridization (FISH) and δ-PCR (FL). RESULTS: LOLA produced signals of the expected sizes for the cell lines. Normal control DNA yielded no signals. A dilution series yielded translocation-specific peaks at dilutions as low as 1%. Signal intensity was log linear to the DNA concentration ( R 2 = 0.94). Furthermore, we were able to detect a LOLA peak in DNA from 53.3% of FL patients and 87.5% of CML patients. The concordance between LOLA, FISH, and δ-PCR in FL was also excellent. CONCLUSIONS: Our results indicate that LOLA is a simple method that is useful for DNA-based detection of translocations in challenging situations, particularly where the breakpoints are not tightly clustered. The assay also has the added benefit of permitting rapid mapping of the breakpoints.